Neurolaw A Conversation with Nita Farahany. - Burton, Howard (Ideas Roadshow Conversations Ser., 2021)
This book is based on an in-depth filmed conversation between Howard Burton and Nita Farahany, Robert O. Everett Distinguished Professor of Law and Professor of Philosophy at Duke University. Nita Farahany is a leading scholar on the ethical, legal, and social implications of emerging technologies. This wide-ranging conversation examines the growing impact of modern neuroscience on the law, deepening our understanding of a wide range of issues, from legal responsibility to the American Constitution's Fifth Amendment privilege against self-incrimination.This carefully-edited book includes an in.